The complete chloroplast genome of Aster sampsonii (Hance) Hemsl, a perennial herb. Issue 9 (2nd September 2021) - Chang, Qinxiang; Li, Yan; Xia, Pengguo; Chen, Xiang
Abstract: Aster sampsonii (Hance) Hemsl is endemic to China. The complete chloroplast genome of Aster sampsonii was studied here. The genome was 152, 686 base pair (bp) in length, containing a large single-copy (LSC) region of 84, 345 bp, a small single-copy region (SSC) of 18, 249 bp and a pair of inverted repeats (IRs) of 25, 046 bp. It contains 132 unique genes, including 86 protein-coding genes, 36 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The GC content of the complete chloroplast genome sequence was 37.3%. Phylogenetic analyses using complete chloroplast genomes showed that Aster sampsonii is most closely related to Aster hypoleucus (NC_046503.1).